Sosialisasi Penerapan Program Kelurahan Maritim Berbasis Edukasi di Kelurahan Untia Untuk Mendukung Program Kampung Nelayan Maju - Muh. Amar; Muh. Irfan Idris; Musmin Musmin; Muhammad Dzuljalalil Ikram; Agus Salim; Muh. Akhyar Al Haris All; Bahri Bahri (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Untia Village, located in Biringkanaya District, Makassar City, is a strategic place because it has the potential of the sea as the main source of livelihood. However, what is found in Untia village is the lack of education in terms of knowledge and skills among the community, causing fishermen in Untia village to still be relatively low in terms of economy, education, environment and health services. Therefore, the PPK Ormawa LDF SC AL FURQAN BEM FIS-H UNM Team provided a solution through an education-based maritime village program oriented towards increasing the economic productivity of fishermen, increasing education, improving environmental quality and health services to create a developed fishing village. The method used in this activity is on the job training (learning while working) together with fishermen and their families to implement the maritime village program. There are 2 (two) outputs produced from PPK Ormawa LDF SC AL FURQAN BEM FIS-H UNM, namely: mandatory outputs include: (1) Thematic Capacity Development and Soft Skills Book, (2) executive summary containing activity descriptions, (3) electronic media publications uploaded to university, faculty and student organization channels, and (4) posters and profiles of activity results. Additional outputs are: (1) real products in the form of fish farming and a mobile library, (2) scientific articles, and (3) mass media publications.